COMPARATIVE STORY OF THE SLAUGHTER OF ABRAHAM’S SON IN THE QURAN AND THE BIBLE - Rahmanto, Oki Dwi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
The story of the slaughter of Abraham's son has attracted a lot of attention among Muslims and non-Muslims. This is because there are different views in the Koran and the Bible regarding who was the figure behind Abraham's slaughter of his son. This research is included in the research library study or literature review. The method taken is descriptive-analysis with a comparative approach between the two books. To produce specific and detailed data, the researcher presents two interpreters in the Koran and the Bible, namely Quraish Shihab as an interpreter of the Koran and Matthew Henry as an interpreter of the Bible. The findings were based on research, namely the first male figure who was slaughtered in the Quran according to the viewpoint of Quraish shihab, namely Ismail. Meanwhile, according to Matthew Henry, that is Isaac. The two factors that cause the difference in interpretation are that the Quraish Shihab in its literature refers to the interpretation of Tabataba'i, which refers to ismail. Apart from that, Quraish Shihab also performed inter-verse munasbahs related to the slaughter of Abraham for his son, while Matthew Henry interpreted the editors in the Bible in a textual way who stated that it was Isaac who was slain. The third impact of interpretation on Muslims and non-Muslims is how they take lessons from the story regarding the meaning of patience, obedience and sincerity. Keywords: Abraham, Slaughter, Al Qur'an and the Bible